2007
DOI: 10.1104/pp.107.101154
|View full text |Cite
|
Sign up to set email alerts
|

Rice Shaker Potassium Channel OsKAT1 Confers Tolerance to Salinity Stress on Yeast and Rice Cells

Abstract: We screened a rice (Oryza sativa L. 'Nipponbare') full-length cDNA expression library through functional complementation in yeast (Saccharomyces cerevisiae) to find novel cation transporters involved in salt tolerance. We found that expression of a cDNA clone, encoding the rice homolog of Shaker family K 1 channel KAT1 (OsKAT1), suppressed the salt-sensitive phenotype of yeast strain G19 (Dena1-4), which lacks a major component of Na 1 efflux. It also suppressed a K 1 -transport-defective phenotype of yeast st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 43 publications
3
83
0
1
Order By: Relevance
“…This model is supported by electrophysiological studies on guard cell protoplasts that demonstrate channel conductances with high (more than an order of magnitude larger) K + selectivity over Na + (Schroeder et al 1984(Schroeder et al , 1987Schroeder 1988;Blatt 1992;Müller-Röber et al 1995;Nakamura et al 1995;Véry et al 1995; see also Véry et al 1998;Lebaudy et al 2008). However, given the multiplicity of inward-rectifying K + channels being expressed in guard cells (Szyroki et al 2001), and that some of these have been demonstrated to be capable of mediating Na + fluxes, albeit mostly in other cell types (Golldack et al 2003;Obata et al 2007;Wang et al 2007), routes for high-capacity Na + entry might exist under some conditions that are not currently accounted for in stomatal guard cell models (Fig. 2).…”
Section: Sodium As a Nutrientmentioning
confidence: 83%
See 1 more Smart Citation
“…This model is supported by electrophysiological studies on guard cell protoplasts that demonstrate channel conductances with high (more than an order of magnitude larger) K + selectivity over Na + (Schroeder et al 1984(Schroeder et al , 1987Schroeder 1988;Blatt 1992;Müller-Röber et al 1995;Nakamura et al 1995;Véry et al 1995; see also Véry et al 1998;Lebaudy et al 2008). However, given the multiplicity of inward-rectifying K + channels being expressed in guard cells (Szyroki et al 2001), and that some of these have been demonstrated to be capable of mediating Na + fluxes, albeit mostly in other cell types (Golldack et al 2003;Obata et al 2007;Wang et al 2007), routes for high-capacity Na + entry might exist under some conditions that are not currently accounted for in stomatal guard cell models (Fig. 2).…”
Section: Sodium As a Nutrientmentioning
confidence: 83%
“…2 Current model of ion transport in guard cells, highlighting Na + -specific mechanisms. K + influx channels (KAT1, KAT2, AKT1, AKT2/3, AtKC1; Pandey et al 2007), integral to stomatal opening, can mediate Na + fluxes in some instances (Schroeder et al 1987;Schroeder 1988;Obata et al 2007), as can members of the KUP/HAK/KT family (Santa-María et al 1997;Takahashi et al 2007), although their involvement in guard cell functioning is currently speculative. Moreover, both classes of transporters can be directly inhibited by Na + (Fu and Luan 1998;Thiel and Blatt 1991).…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…Altos teores de Na, ou baixa relação K/Na no solo, podem deflagrar uma série de processos enzimáticos no citoplasma da planta, permitindo a competição entre o Na e o K pelos sítios de absorção (Obata et al, 2007), sendo a capacidade da planta em manter alta a relação K/Na no citosol premissa básica para o adequado crescimento em solos salinos (Glenn et al, 1999). As concentrações foliar de íons podem ser usados para distinção entre variedades "Na-inclusoras" e "Na-evitadoras".…”
Section: Absorção De Cátions Pelo Arrozunclassified
“…10 OsKAT1 was already identified to enhance the salt stress tolerance when it is constitutively overexpressed. 5 However, functional analysis of those genes as well as the electrophysiological characteristics of the channels has not been conducted yet. Those genes have very similar amino acid sequences except that OsKAT1 has shorter C-terminal region compared with others.…”
mentioning
confidence: 99%
“…3 In higher plants, several shaker-like potassium channels were also reported. [4][5][6][7][8][9] In our recent publication, 11 shaker-like potassium channels were predicted in rice by using homology search analysis. Among them, three genes are likely AtKAT1 homologs, and those are named as OsKAT1, OsKAT2, and OsKAT3.…”
mentioning
confidence: 99%